DAMPAK IMPOR GULA PASIR TERHADAP HARGA GULA PASIR DOMESTIK DI INDONESIA - Ermi Tety; Ica Eganisa; Deby Kurnia (Fakultas Pertanian, Universitas Riau, 2022)
White sugar is one of Indonesia's most essential food commodities. The government conducts import activities in an effort to stabilize the price of domestic sugar because national sugar production does not meet the demand. Domestic sugar prices reached the highest point in history in 2020, with prices ranging from Rp. 16.000 per kilogram to Rp. 21.000 per kilogram. The government has also imported 5.5 million tons of white sugar in 2020. The goals of this research are to (1) determine the conditions of white sugar imports in Indonesia from 2000 to 2020, (2) project the volume of white sugar imports and domestic white sugar prices in Indonesia for 2021-2025, and (3) analyze the impact of imported white sugar on domestic white sugar prices in Indonesia. The data used in this study is secondary data and processed using descriptive statistical analysis, simple exponential smoothing trend analysis, and multiple linear regression analysis. The results of this research are: (1) the volume of white sugar imports in Indonesia fluctuated and tended to increase from 2000 to 2020, (2) the projected volume of white sugar imports in 2021-2025 will increase by 0.26 percent per year, while domestic white sugar prices will increase by 3.3 percent per year, (3), the volume of white sugar imports, world sugar prices, sugar import duty rates, and white sugar consumption have a large partial effect on domestic white sugar prices with a confidence level of 97.68 percent. Otherwise, the domestic white sugar production has no effect on domestic white sugar prices